Morphology and biochemical variables in rats’placentas with pregestational visceral obesity - Catherina Capote Guitian; Nínive Núñez López; Gladys González Aguilar; Amanda Llanes Tamayo; Maryanis Mosqueda Furones; Gipsis Suárez Román (Medisur)
Foundation: Placental analysis is key to understand the development of fetal complications in pregestational visceral obesity. Objective: to determine the morphofunctional characteristics, lipid content and redox status of rats’ placentas with pregestational visceral obesity. Methods: female Wistar rats were studied that received monosodium glutamate (4 mg/g of body weight) to induce obesity or 0.9% NaCl (controls) subcutaneously in the neonatal period. Obesity was confirmed at 90 days of life and at 120 days they were mated overnight with healthy males of the same strain. Day 0 of gestation was considered the morning in which copulation was confirmed by the presence of sperm in the douching. Euthanasia was performed on days 14 and 17 of gestation and fetal weight and macroscopic, microscopic and biochemical variables at the placental level were determined. Results: On day E17, a decrease in fetal weight and placental diameters was observed in the group of obese rats, as well as an increase in placental thickness and index. At the microscopic level, the placentas showed a decrease in the total area of the sagittal half and the labyrinth on day E14. An increase in the area of the trophoblast and a decrease in the area of maternal blood in the labyrinth and an increase in glycogen reserve cells in the junction zone were observed at both times of development. Conclusions: The rats’ placentas with pregestational visceral obesity induced by monosodium glutamate present structural alterations that show a decrease in maternal-fetal exchange.